Process for the epoxidation of pinene
Patent Information
- Application Number
- CN202211320464.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-10-26
AI Technical Summary
[0003]文献报道(Catalysis Communications,2009,11:106-109),以Co3O4为催化剂,空气为氧化剂,N,N-二甲基甲酰胺为溶剂在超声波环境中催化α-蒎烯制备得到α-环氧蒎烷的选择性可达~94%,但是,大量溶剂的使用、超声波的反应环境以及催化剂稳定性不足的特点限制了其进一步的应用
[0009]本发明所述方法可以实现由蒎烯环氧化直接生产相应环氧蒎烷,具有高产物选择性,同时具有催化反应条件温和、催化剂稳定性高的特点。
Smart Images

Figure CN117964581B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of olefin epoxidation reactions, and more specifically to a method for pinene epoxidation reaction. Background Technology
[0002] α-Pinene is a fundamental organic chemical substance and an important raw material for the synthesis of fragrances, mainly produced from my country's abundant turpentine oil resources. High-value derivatives such as α-epoxypinene and bornenaldehyde can be obtained from α-pinene. α-epoxypinene can be prepared by epoxidation of α-pinene, and further isomerization yields bornenaldehyde. Currently, some studies have employed Ti-MCM-22 catalysis for the highly selective (≥96%) synthesis of α-epoxypinene to bornenaldehyde, but the most crucial step now is how to stably and efficiently achieve the epoxidation of α-pinene to prepare α-epoxypinene (Catal. Sci. Technol., 2018, 8, 4690-4701).
[0003] Literature reports (Catalysis Communications, 2009, 11: 106-109) that using Co3O4 as a catalyst, air as an oxidant, and N,N-dimethylformamide as a solvent in an ultrasonic environment, the selectivity for preparing α-epoxypinene from α-pinene can reach ~94%. However, the use of large amounts of solvent, the ultrasonic reaction environment, and the insufficient stability of the catalyst limit its further application. Literature uses Mn(TPP)Cl or Mn(TDCPP)Cl as catalysts and potassium persulfate / sodium hypochlorite as oxidants, achieving complete conversion of α-pinene at room temperature with a selectivity of up to 96% for the epoxide. However, the catalyst preparation process is complex and costly (Journal of Catalysis, 2002, 206: 349-357). CN1438222A discloses the synthesis of α-epoxypinene using a fourth-period transition metal salt as a catalyst and stirring at room temperature for 45-55 hours. Although α-pinene can be completely converted, the product selectivity is only 80%. CN112608287A discloses a method for synthesizing epoxide pinane from pinene. This method uses a mixture of hydrogen peroxide and acetic anhydride to generate peracetic acid, followed by a pinene epoxidation reaction. However, in actual operation, the ratio of hydrogen peroxide to acetic anhydride needs to be strictly controlled to avoid dangerous factors caused by excessive peracetic acid content. Furthermore, this reaction requires the introduction of large amounts of toxic and carcinogenic solvents such as dichloroethane. CN114591268A uses heteropolyacid salts as epoxidation catalysts, reporting a yield of α-epoxide pinane as high as 96.9%. However, it is known that heteropolyacid salt catalysts generally suffer from insufficient stability, thus their practical application still faces challenges.
[0004] Zeolite molecular sieves are a class of materials with unique pore structures and acidic properties. Their large external surface area allows them to serve as supports for various metal heteroatoms, thus exhibiting multiple types of active sites and broadening their application range. Furthermore, zeolite molecular sieves generally exhibit good hydrothermal stability and stable catalytic performance, and have been applied in various practical industrial operations. Literature reports that Ti-MCM-41, using H2O2 as an oxidant, can catalyze the synthesis of verbenaone in 50% yield and borneol in 32% yield from α-pinene, with a conversion rate of only 20% (Catalysis Today, 2008, 133:678-683). Literature reports (Catalysis Letters, 1997, 4: 171-176) indicate that the epoxidation of α-pinene to α-epoxypinene still suffers from low yields (≤15%) and low selectivity (≤80%) when using Ti-MCM-41, Ti-HMS, and catalysts further modified from both. For this type of catalyst, the urgent problem to be solved is modification methods to obtain catalysts with high catalytic activity and high selectivity, thereby providing practical guidance for the green synthesis of α-epoxypinene from the epoxidation of α-pinene. Summary of the Invention
[0005] The purpose of this invention is to overcome the problems existing in the prior art and provide a method for the epoxidation reaction of pinene, which can directly produce the corresponding epoxide pinene by epoxidation of pinene and has high product selectivity.
[0006] To achieve the above objectives, the present invention provides a method for the epoxidation reaction of pinene, the method comprising: contacting pinene, at least one oxidant, and optionally at least one solvent with a titanium-containing SiO2 catalyst under epoxidation reaction conditions to obtain a reaction product;
[0007] The titanium-containing SiO2 catalyst comprises amorphous SiO2, titanium, and fluorine.
[0008] The beneficial effects of the present invention through the above technical solution include:
[0009] The method described in this invention can directly produce the corresponding epoxide pinane from pinene epoxidation, with high product selectivity, mild catalytic reaction conditions, and high catalyst stability. Attached Figure Description
[0010] Figure 1 This is the UV-VIS image of the titanium-containing SiO2 catalyst prepared in Example 1;
[0011] Figure 2 This is the UV-VIS image of the titanium-containing SiO2 catalyst prepared in Comparative Example 1;
[0012] Figure 3 The image shows the UV-VIS pattern of Ti-MCM-41 prepared in Comparative Example 2.
[0013] Figure 4 This is the XPS image of the titanium-containing SiO2 catalyst prepared in Example 1. Detailed Implementation
[0014] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0015] The present invention provides a method for the epoxidation reaction of pinene, the method comprising: contacting pinene, at least one oxidant, and optionally at least one solvent with a titanium-containing SiO2 catalyst under epoxidation reaction conditions to obtain a reaction product;
[0016] The titanium-containing SiO2 catalyst comprises amorphous SiO2, titanium, and fluorine.
[0017] In this invention, unless otherwise specified, "optional" means containing or not containing, adding or not adding, or using or not using. Specifically, the reaction described in this invention may or may not involve the addition of a solvent.
[0018] The present invention does not impose any particular limitation on the order of addition of the pinene, oxidant, solvent, and titanium-containing SiO2 catalyst; they can be added together or separately. The embodiments of the present invention use the method of adding them together as an example.
[0019] Preferably, the method further includes: stirring the added materials to mix them evenly.
[0020] The present invention does not impose any particular limitation on the stirring time and speed, which can be appropriately selected according to the specific circumstances, as long as the purpose of uniform mixing can be achieved.
[0021] According to the present invention, preferably, the conditions for the epoxidation reaction include: a temperature of 60-125°C, more preferably 60-110°C; and a pressure of 0.01-1 MPa, more preferably 0.1-0.5 MPa.
[0022] Preferably, the epoxidation reaction is carried out under stirring conditions.
[0023] The present invention does not impose any particular limitation on the stirring time and speed, which can be appropriately selected according to the specific circumstances.
[0024] According to a specific embodiment of the present invention, pinene, titanium-containing SiO2 catalyst, oxidant, solvent and additives are placed in a round-bottom flask equipped with a reflux condenser and a magnetic stir bar. After the solution is stirred and mixed, the round-bottom flask is transferred to a constant temperature water bath for reaction.
[0025] According to the present invention, preferably, the mass ratio of titanium-containing SiO2 catalyst:pinene:oxidant is 1:(25-150):(5-50), more preferably 1:(50-120):(10-20). This preferred embodiment helps maintain high levels of reaction conversion, target product selectivity, and catalyst stability.
[0026] According to the present invention, preferably, the pinene is α-pinene, and the reaction product is α-epoxypinene.
[0027] According to the present invention, preferably, the oxidant is a peroxide, more preferably hydrogen peroxide, an organic peroxide, and a peracid, and more preferably tert-butyl hydroperoxide decane and / or cumene hydroperoxide. This preferred embodiment facilitates the diffusion of the oxidant to the active sites of the catalyst and promotes the conversion of the oxidant.
[0028] The present invention allows for a wide range of solvent selection. Preferably, the solvent is selected from at least one of water, C1-C6 alcohols, and C6-C12 aromatic hydrocarbons, and more preferably tert-butanol and / or cumene. This preferred embodiment facilitates more thorough and uniform mixing of the reactant molecules.
[0029] According to the present invention, preferably, the mass ratio of titanium-containing SiO2 catalyst to solvent is 1:(5-45), more preferably 1:(5-20).
[0030] According to the present invention, preferably, the contact is carried out in the presence of at least one adjuvant.
[0031] According to the present invention, preferably, the mass ratio of titanium-containing SiO2 catalyst to additive is 1:(0.05-1), more preferably 1:(0.05-0.25).
[0032] The adjuvant described in this invention helps maintain the stability of pinene molecules, effectively preventing isomerization reactions and thus promoting the main reaction. Preferably, the adjuvant is selected from at least one of sodium carbonate, sodium bicarbonate, potassium carbonate, and potassium bicarbonate.
[0033] According to the present invention, preferably, the method further includes: distilling the contacted materials to obtain the reaction product.
[0034] The present invention does not impose any particular limitation on the distillation conditions, and can refer to the methods commonly used in the art, as long as the component at 185±15℃ can be distilled out.
[0035] According to the present invention, preferably, the molar ratio of Si / Ti in the titanium-containing SiO2 catalyst is 25-250, more preferably 45-200; the molar ratio of Si / F is 30-120, more preferably 40-90. These preferred ratios are more conducive to improving reactant conversion and product selectivity.
[0036] In this invention, the molar ratio of Si / Ti is determined by ICP method, and the molar ratio of Si / F is determined by XPS method.
[0037] In this invention, the ICP testing method specifically involves using a Varian-2000 analyzer to analyze the titanium, silicon, sodium, iron, and potassium content in the titanium-containing SiO2 catalyst. Before testing, the sample is dissolved in hydrofluoric acid solution.
[0038] In this invention, the XPS testing method specifically employs an Axis Ultra DLD X-ray photoelectron spectrometer manufactured by Kratos, UK, with a monochromatic Al target. The voltage is 15 kV, and the current is 10 mA. The full-spectrum pass energy is 160 eV, and the elemental spectrum pass energy is 40 eV.
[0039] According to the present invention, preferably, the titanium-containing SiO2 catalyst exhibits an absorption peak at 210-230 nm as characterized by UV-VIS. This indicates successful Ti loading. Furthermore, the Ti species is primarily Ti(OSi)4, which is in a favorable state, beneficial for improving catalytic reaction performance.
[0040] According to the present invention, preferably, the sodium content, iron content, and potassium content in the titanium-containing SiO2 catalyst are below 50 ppm, below 50 ppm, and below 50 ppm. The catalyst provided by the present invention has a low impurity content, which is beneficial for improving the activity of the titanium-containing SiO2 catalyst.
[0041] According to the present invention, preferably, the preparation method of the titanium-containing SiO2 catalyst includes:
[0042] (1) Mix amorphous SiO2 powder with a fluorine source in an alkaline solution to obtain fluorine-containing SiO2 solid;
[0043] (2) The fluorine-containing SiO2 solid is loaded with titanium under a protective gas atmosphere to obtain a titanium-containing SiO2 catalyst precursor;
[0044] (3) The titanium-containing SiO2 catalyst precursor is subjected to water vapor treatment and silane vapor treatment in a protective gas atmosphere to obtain the titanium-containing SiO2 catalyst.
[0045] According to the present invention, preferably, the amounts of amorphous SiO2, titanium source, and fluorine source are such that the molar ratio of Si / Ti in the prepared titanium-containing SiO2 catalyst is 25-250, and the molar ratio of Si / F is 30-120.
[0046] According to the present invention, preferably, the amounts of amorphous SiO2, titanium source, and fluorine source are such that the molar ratio of Si / Ti in the prepared titanium-containing SiO2 catalyst is 45-200, and the molar ratio of Si / F is 40-90.
[0047] According to the present invention, preferably, the amorphous SiO2 contains sodium, iron and potassium, wherein the sodium content is less than 1000 ppm, the iron content is less than 1000 ppm, and the potassium content is less than 1000 ppm.
[0048] According to the present invention, preferably, the specific surface area of the amorphous SiO2 is 300-500 m² / g. 2 / g, pore volume of 1-1.8cm³ 3 / g, with an average pore size of 5-10nm.
[0049] This invention does not impose any particular limitation on the source of the amorphous SiO2, as long as the above conditions are met. It can be obtained commercially or prepared using existing methods.
[0050] According to the present invention, preferably, the mixing in step (1) includes: first mixing amorphous SiO2 powder with an alkaline solution, and then mixing it with a fluorine source. This preferred embodiment facilitates the subsequent introduction of the fluorine source and effectively removes sodium, potassium, and iron impurities from the amorphous SiO2.
[0051] The present invention does not particularly limit the number of times the first mixing is performed; it can be performed once or multiple times, provided that the sodium content, iron content, and potassium content in the amorphous SiO2 are below 50 ppm. Preferably, the first mixing is performed 1-5 times, more preferably 3-5 times.
[0052] When the first mixing is performed multiple times, a fluorine source can be introduced during the last mixing to perform a second mixing.
[0053] Preferably, except for the final first mix, the materials obtained from each subsequent first mix are washed and filtered. The present invention does not particularly limit the conditions for washing and filtration, and these conditions can be performed using conventional techniques in the art; further details will not be elaborated upon here.
[0054] According to the present invention, preferably, the mixing conditions in step (1) include: a temperature of 25-70°C, more preferably 40-55°C; and a time of 0.5-8 h, more preferably 1-5 h. This preferred embodiment facilitates the introduction of the fluorine source.
[0055] According to the present invention, preferably, the molar ratio of amorphous SiO2 to fluorine source is 1:30-150, more preferably 1:30-45, wherein the fluorine source is calculated as elemental F. This preferred embodiment is beneficial for improving the catalytic performance of the catalyst.
[0056] According to the present invention, preferably, the weight ratio of the amorphous SiO2 to the alkaline solution is 1:5-50, more preferably 1:10-35.
[0057] According to the present invention, preferably, the molar concentration of the alkaline solution is 0.5-2.5 mol / L.
[0058] According to the present invention, preferably, the base is an inorganic base and / or an organic base; the inorganic base is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate; the organic base is selected from at least one of ethylamine, methylamine, n-butylamine, and tetrapropylammonium bromide.
[0059] More preferably, the alkali is selected from at least one of sodium hydroxide, potassium hydroxide, and ethylamine.
[0060] The present invention allows for a wide range of fluorine source selection, as long as fluorine can be provided. Preferably, the fluorine source is hydrofluoric acid and / or a fluorine-containing soluble salt, and is more preferably selected from at least one of ammonium fluoride, potassium fluoride, and sodium fluoride.
[0061] In this invention, "soluble" means that it can be directly dissolved in a solvent, or dissolved in a solvent with the help of a co-solvent.
[0062] Preferably, the method further includes drying the mixture obtained in step (1) to obtain fluorine-containing SiO2 solid. The present invention does not particularly limit the drying method; it can be carried out according to conventional techniques in the art, and will not be elaborated further here.
[0063] According to the present invention, preferably, the conditions for loading titanium in step (2) include: a temperature of 280-750℃, preferably 300-600℃; and a time of 0.5-6h, preferably 0.5-3h.
[0064] This invention allows for a wide range of titanium source selection; the titanium source can be gaseous or liquid. Preferably, a gaseous titanium source is used. More preferably, the titanium source is titanium tetrachloride. This preferred embodiment results in high titanium utilization.
[0065] According to a specific embodiment of the present invention, a protective gas is first passed through a storage tank containing saturated titanium tetrachloride vapor, and then contacted with the fluorine-containing SiO2 solid obtained in step (1).
[0066] According to the present invention, preferably, the flow rate of the protective gas is 50-300 mL / min, more preferably 60-100 mL / min, relative to 1 g of fluorine-containing SiO2 solid. Using this preferred embodiment, heteroatom titanium can be easily and conveniently loaded onto SiO2 with high loading efficiency.
[0067] The present invention determines the amount of titanium loaded by controlling the flow rate of the protective gas through a storage tank containing saturated titanium tetrachloride vapor and the titanium loading time.
[0068] The present invention allows for a wide range of choices for the protective gas, which can be conventional choices in the art. According to the present invention, preferably, the protective gas is selected from at least one of nitrogen, helium, and argon; for economic reasons, nitrogen is preferred.
[0069] The range of protective gas types and dosages mentioned in the various steps of this article can be the same or different, but preferably the same.
[0070] According to the present invention, preferably, the method further includes: before the titanium loading in step (2), the fluorine-containing SiO2 solid product is treated under a protective gas atmosphere, wherein the treatment conditions include: a temperature of 150-300℃, preferably 200-300℃; and a time of 1-6h, preferably 1-3h.
[0071] The steam treatment described in this invention helps to eliminate residual Ti-Cl bonds and fragmented SiO2 on SiO2, and can also form Si-OH groups, which is beneficial for subsequent silanization treatment. Preferably, the conditions for steam treatment in step (3) include: a temperature of 80-600℃, preferably 80-500℃; and a time of 0.5-6h, preferably 0.5-3h.
[0072] According to a specific embodiment of the present invention, the protective gas is first passed through a storage tank containing saturated water vapor, and then contacted with the titanium-containing SiO2 catalyst precursor obtained in step (2).
[0073] The silane vapor treatment described in this invention is beneficial for improving the lipophilicity of the catalyst. Preferably, the conditions for the silane vapor treatment include: a temperature of 150-350℃, more preferably 150-250℃; and a time of 0.5-10h, more preferably 0.5-5h.
[0074] According to one specific embodiment of the present invention, a protective gas is first passed through a storage tank containing saturated silane vapor, and then contacted with the product obtained by steam treatment.
[0075] The amount of water vapor used in the water vapor treatment and the amount of silane reagent used in the silane vapor treatment are determined by the flow rate of the protective gas through the storage tank containing saturated vapor and their respective treatment times.
[0076] The catalyst described in this invention can be reused after regeneration. This invention does not particularly limit the regeneration conditions; conventional methods in the art can be used. Preferably, regeneration is performed by washing followed by drying.
[0077] Preferably, the washing agent used is cumene, and the washing conditions are such that the filtrate is close to neutral, i.e., pH = 7-8.
[0078] The present invention does not have any particular limitation on the drying process, which can be carried out in accordance with conventional technical means in the field, and will not be described in detail here.
[0079] The present invention will be described in detail below through embodiments.
[0080] In the following preparation examples, the methods for determining Si / Ti and Si / F are as described above.
[0081] All reagents used in the following preparation examples are commercially available and of analytical grade.
[0082] In the following preparation examples, the specific surface area of amorphous SiO2 is 350 m² / g. 2 / g, pore volume is 1.18cm³ 3 / g, with an average pore size of 7nm, wherein the sodium content is below 1000ppm, the iron content is below 1000ppm, and the potassium content is below 1000ppm.
[0083] In the following examples, the content of the reaction liquid components was analyzed by gas chromatography-7890A, and the yield of α-epoxypine was measured. α-环氧蒎烷 Selectivity of α-epoxypine α-环氧蒎烷 The calculation formula is as follows:
[0084] Yield α-环氧蒎烷 =N α-环氧蒎烷 / N 氧化剂0 ×100%
[0085] S α-环氧蒎烷 =N α-环氧蒎烷 / (N 氧化剂0 -N 氧化剂1 )×100%
[0086] Where, N α-环氧蒎烷 N represents the molar amount of α-epoxypinene obtained at the end of the reaction. 氧化剂0 and N 氧化剂1 These represent the initial molar amount of oxidant in the reaction solution components and the final molar amount of oxidant after the reaction, respectively.
[0087] Preparation Example 1
[0088] Preparation of titanium-containing SiO2 catalyst: First, amorphous SiO2 powder was uniformly mixed with 2 mol / L ethylamine solution at a mass ratio of SiO2:alkali solution = 1:18. The mixture was treated in a 50℃ water bath for 1 hour. The solid product obtained after washing and filtration was repeated three times. In the fourth treatment, ammonium fluoride was introduced at a molar ratio of SiO2:ammonium fluoride = 1:30. The solid product obtained in the fourth treatment was then dried to obtain fluorinated SiO2 solid. 2.5 g of fluorinated SiO2 solid was placed in a quartz tube and nitrogen gas was introduced at a flow rate of 150 mL / min. The reaction was carried out at 250℃ for 2 hours. Then, the temperature was raised to 400℃, and after the temperature stabilized, the nitrogen gas was switched to pass through a storage tank containing saturated titanium tetrachloride vapor before flowing into the quartz tube for a reaction for 1 hour to obtain the titanium-containing SiO2 catalyst precursor. When the process is about to end, the temperature is lowered to 250℃, and the nitrogen valve is switched to allow nitrogen to pass through a storage tank containing saturated water vapor before flowing into a quartz tube for reaction for 2 hours. Then, the temperature is lowered to 200℃, and the nitrogen valve is switched to allow nitrogen to pass through a storage tank containing saturated hexamethyldisilazane vapor before flowing into a quartz tube for reaction for 3 hours, resulting in a titanium-containing SiO2 catalyst with Si / Ti = 124, Si / F = 66, sodium content below 50 ppm, iron content below 50 ppm, and potassium content below 50 ppm.
[0089] UV-VIS pattern of titanium-containing SiO2 catalyst, as shown Figure 1 As shown, an absorption peak appears at 215 nm, indicating successful Ti loading. Furthermore, the Ti species is primarily Ti(OSi)4, which is in a favorable state, beneficial for improving catalytic reaction performance.
[0090] An example XPS energy spectrum of a titanium-containing SiO2 catalyst is given, such as... Figure 4 As shown, it can be seen that at 687 eV, the value belonging to F appears. 1s The spectral peaks indicate that F is implanted into SiO2.
[0091] Preparation Example 2
[0092] Preparation of titanium-containing SiO2 catalyst: First, amorphous SiO2 powder was uniformly mixed with 1.5 mol / L potassium hydroxide solution at a mass ratio of SiO2:alkali solution = 1:25. The mixture was then treated in a water bath at 45℃ for 1 hour. The solid product obtained after washing and filtration was repeated three times. In the fourth treatment, ammonium fluoride was introduced at a molar ratio of SiO2:ammonium fluoride = 1:35. The solid product obtained in the fourth treatment was then dried to obtain fluorine-containing SiO2 solid. 2.5 g of fluorine-containing SiO2 solid was placed in a quartz tube and nitrogen gas was introduced at a flow rate of 150 mL / min. The reaction was carried out at 250℃ for 2 hours. Then, the temperature was raised to 400℃, and after the temperature stabilized, the nitrogen gas was switched so that the nitrogen gas first passed through a storage tank containing saturated titanium tetrachloride vapor and then flowed into the quartz tube to react for 1 hour, obtaining the titanium-containing SiO2 catalyst precursor. When the process is about to end, maintain the temperature at 400°C and switch the nitrogen valve to pass nitrogen first through a storage tank containing saturated water vapor, and then into a quartz tube to react for 2 hours. Then, cool down to 200°C and switch the nitrogen valve again to pass nitrogen first through a storage tank containing saturated hexamethyldisilazane vapor, and then into a quartz tube to react for 3 hours to obtain a titanium-containing SiO2 catalyst with Si / Ti = 118 and Si / F = 54.
[0093] The UV-VIS pattern of the titanium-containing SiO2 catalyst is similar to that in Example 1.
[0094] Preparation Example 3
[0095] Preparation of titanium-containing SiO2 catalyst: First, amorphous SiO2 powder was uniformly mixed with 2 mol / L ethylamine solution at a mass ratio of SiO2:alkali solution = 1:18. The mixture was treated in a 50℃ water bath for 1 hour. The solid product obtained after washing and filtration was repeated three times. In the fourth treatment, potassium fluoride was introduced at a molar ratio of SiO2:potassium fluoride = 1:40. The solid product obtained in the fourth treatment was then dried to obtain fluorine-containing SiO2 solid. 2.5 g of fluorine-containing SiO2 solid was placed in a quartz tube and nitrogen gas was introduced at a flow rate of 150 mL / min. The reaction was carried out at 250℃ for 2 hours. Then, the temperature was raised to 400℃, and after the temperature stabilized, the nitrogen gas was switched to pass through a storage tank containing saturated titanium tetrachloride vapor before flowing into the quartz tube for a reaction for 1 hour to obtain the titanium-containing SiO2 catalyst precursor. When the process is about to end, the temperature is lowered to 180°C, and the nitrogen valve is switched to allow nitrogen to pass through a storage tank containing saturated water vapor before flowing into a quartz tube for reaction for 2.5 hours. Then, the temperature is raised to 200°C, and the nitrogen valve is switched to allow nitrogen to pass through a storage tank containing saturated hexamethyldisilazane vapor before flowing into a quartz tube for reaction for 3 hours, resulting in a titanium-containing SiO2 catalyst with Si / Ti = 128 and Si / F = 52.
[0096] The UV-VIS pattern of the titanium-containing SiO2 catalyst is similar to that in Example 1.
[0097] Preparation Example 4
[0098] Preparation of titanium-containing SiO2 catalyst: First, amorphous SiO2 powder was uniformly mixed with 2.5 mol / L sodium hydroxide solution at a mass ratio of SiO2:alkali solution = 1:30. The mixture was treated in a 50℃ water bath for 1 hour. The solid product obtained after washing and filtration was repeated three times. In the fourth treatment, potassium fluoride was introduced at a molar ratio of SiO2:potassium fluoride = 1:30. The solid product obtained in the fourth treatment was then dried to obtain fluorine-containing SiO2 solid. 2.5 g of fluorine-containing SiO2 solid was placed in a quartz tube and nitrogen gas was introduced at a flow rate of 150 mL / min. The reaction was carried out at 250℃ for 2 hours. Then, the temperature was raised to 400℃, and after the temperature stabilized, the nitrogen gas was switched to pass through a storage tank containing saturated titanium tetrachloride vapor before flowing into the quartz tube for a reaction of 2.5 hours to obtain the titanium-containing SiO2 catalyst precursor. When the process is about to end, the temperature is maintained at 400°C, and the nitrogen valve is switched to allow nitrogen to pass through a storage tank containing saturated water vapor before flowing into a quartz tube for reaction for 2 hours. Then, the temperature is lowered to 200°C, and the nitrogen valve is switched to allow nitrogen to pass through a storage tank containing saturated hexamethyldisilazane vapor before flowing into a quartz tube for reaction for 3 hours, resulting in a titanium-containing SiO2 catalyst with Si / Ti = 51 and Si / F = 48.
[0099] The UV-VIS pattern of the titanium-containing SiO2 catalyst is similar to that in Example 1.
[0100] Preparation of Comparative Example 1
[0101] The preparation method was followed as in Example 1, except that no fluorine source was introduced. The catalyst had a Si / Ti ratio of 140.
[0102] UV-VIS image of titanium-containing SiO2 catalyst. Figure 2 As shown, an absorption peak appears at 300-350 nm, indicating that a large number of Ti atoms condense and cover the catalyst as TiO2 species, affecting the state of the Ti species.
[0103] Preparation of Comparative Example 2
[0104] The Ti-MCM-41 catalyst was synthesized according to the reference (Catalysis Letters, 1997, 4: 171-176), and the Si / Ti ratio of the Ti-MCM-41 catalyst was 48.
[0105] UV-VIS pattern of the catalyst, as shown Figure 3 As shown, the absorption peak at 235-255 nm indicates that Ti on the catalyst is mainly Ti(OSi)3OH, and the Ti species on the catalyst are in poor state.
[0106] Examples 1-4, Comparative Examples 1-2
[0107] The titanium-containing SiO2 catalysts prepared in Preparation Examples 1-4 and Comparative Examples 1-2 were applied to the epoxidation reaction of α-pinene to synthesize α-epoxypinene. 5g of titanium-containing SiO2 catalyst, 50g of cumene solution, 250g of α-pinene, 0.5g of sodium bicarbonate, and 83.6g of cumene hydrogen peroxide were weighed into a round-bottom flask equipped with a reflux condenser and magnetic stirrer. After stirring to mix the solution, the flask was transferred to a 65°C constant temperature water bath, and magnetic stirring was started. The reaction time was calculated, and after 2 hours, the flask was immediately cooled. The catalyst and reaction solution were then separated by centrifugation. The catalyst was repeatedly washed with cumene as a washing agent and then dried for the next cycle of reaction, maintaining the same catalyst-to-reactant ratio as the first cycle. For the reaction solution, a small amount of the reaction solution was analyzed by gas chromatography to determine the molar amount of α-epoxypine. The remaining molar amount of cumene hydrogen peroxide in the reaction solution was titrated with 0.1 mol / L sodium thiosulfate. Based on this, the yield can be calculated. α-环氧蒎烷 and S α-环氧蒎烷 The results are shown in Table 1.
[0108] Example 5
[0109] The titanium-containing SiO2 catalyst prepared in Example 1 was applied to the epoxidation reaction of α-pinene to synthesize α-epoxypinene. 5 g of titanium-containing SiO2 catalyst, 50 g of cumene solution, 375 g of α-pinene, 0.5 g of sodium bicarbonate, and 83.6 g of cumene hydrogen peroxide solution were weighed into a round-bottom flask equipped with a reflux condenser and magnetic stirrer. After stirring to mix the solution, the flask was transferred to a 65°C constant-temperature water bath, and magnetic stirring was started. The reaction time was calculated, and after 2 hours, the flask was immediately cooled. The catalyst and reaction solution were then separated by centrifugation. The catalyst was repeatedly washed with cumene as a washing agent and then dried for the next cycle of reaction, maintaining the same catalyst-to-reactant ratio as the first cycle. For the reaction solution, a small amount of the reaction solution was analyzed by gas chromatography to determine the molar amount of α-epoxypine. The remaining molar amount of cumene hydrogen peroxide in the reaction solution was titrated with 0.1 mol / L sodium thiosulfate. Based on this, the yield can be calculated. α-环氧蒎烷 and S α-环氧蒎烷 The results are shown in Table 1.
[0110] Example 6
[0111] The titanium-containing SiO2 catalyst prepared in Example 1 was used to synthesize α-epoxypinene via the epoxidation of α-pinene. 5 g of titanium-containing SiO2 catalyst, 50 g of cumene solution, 520 g of α-pinene, 0.5 g of sodium bicarbonate, and 83.6 g of cumene hydrogen peroxide solution were weighed into a round-bottom flask equipped with a reflux condenser and a magnetic stirrer. After stirring to mix the solution, the flask was transferred to a 65°C constant-temperature water bath, and magnetic stirring was started. The reaction time was calculated, and after 2 hours, the flask was immediately cooled. The catalyst and reaction solution were then separated by centrifugation. The catalyst was repeatedly washed with cumene as a washing agent and then dried for the next cycle of reaction, maintaining the same catalyst-to-reactant ratio as the first cycle. For the reaction solution, a small amount of the reaction solution was analyzed by gas chromatography to determine the molar amount of α-epoxypine. The remaining molar amount of cumene hydrogen peroxide in the reaction solution was titrated with 0.1 mol / L sodium thiosulfate. Based on this, the yield can be calculated. α-环氧蒎烷 and S α-环氧蒎烷 The results are shown in Table 1.
[0112] Example 7
[0113] The titanium-containing SiO2 catalyst prepared in Example 1 was used to synthesize α-epoxypinene via the epoxidation of α-pinene. 5g of titanium-containing SiO2 catalyst, 50g of cumene solution, 250g of α-pinene, 0.5g of sodium bicarbonate, and 83.6g of cumene hydrogen peroxide were weighed into a round-bottom flask equipped with a reflux condenser and a magnetic stirrer. After stirring to mix the solution, the flask was transferred to a 75°C constant-temperature water bath, and magnetic stirring was started. The reaction time was calculated, and after 2 hours, the flask was immediately cooled. The catalyst and reaction solution were then separated by centrifugation. The catalyst was repeatedly washed with cumene as a washing agent and then dried for the next cycle of reaction, maintaining the same catalyst-to-reactant ratio as the first cycle. For the reaction solution, a small amount of the reaction solution was analyzed by gas chromatography to determine the molar amount of α-epoxypine. The remaining molar amount of cumene hydrogen peroxide in the reaction solution was titrated with 0.1 mol / L sodium thiosulfate. Based on this, the yield can be calculated. α-环氧蒎烷 and S α-环氧蒎烷 The results are shown in Table 1.
[0114] Example 8
[0115] The titanium-containing SiO2 catalyst prepared in Example 1 was used to synthesize α-epoxypinene via the epoxidation of α-pinene. 5g of titanium-containing SiO2 catalyst, 50g of cumene solution, 250g of α-pinene, 0.5g of sodium bicarbonate, and 83.6g of cumene hydrogen peroxide were weighed into a round-bottom flask equipped with a reflux condenser and a magnetic stirrer. After stirring to mix the solution, the flask was transferred to an 85°C constant-temperature water bath, and magnetic stirring was started. The reaction time was calculated, and after 2 hours, the flask was immediately cooled. The catalyst and reaction solution were then separated by centrifugation. The catalyst was repeatedly washed with cumene as a washing agent and then dried for the next cycle of reaction, maintaining the same catalyst-to-reactant ratio as the first cycle. For the reaction solution, a small amount of the reaction solution was analyzed by gas chromatography to determine the molar amount of α-epoxypine. The remaining molar amount of cumene hydrogen peroxide in the reaction solution was titrated with 0.1 mol / L sodium thiosulfate. Based on this, the yield can be calculated. α-环氧蒎烷 and S α-环氧蒎烷 The results are shown in Table 1.
[0116] Example 9
[0117] The titanium-containing SiO2 catalyst prepared in Example 1 was used to synthesize α-epoxypinene via the epoxidation of α-pinene. 5 g of titanium-containing SiO2 catalyst, 50 g of cumene solution, 250 g of α-pinene, 0.5 g of sodium bicarbonate, and 83.6 g of cumene hydrogen peroxide were weighed into a round-bottom flask equipped with a reflux condenser and a magnetic stirrer. After stirring to mix the solution, the flask was transferred to a 65°C constant-temperature water bath, and magnetic stirring was started. The reaction time was calculated, and after 1 hour of reaction, the flask was immediately cooled. The catalyst and reaction solution were then separated by centrifugation. The catalyst was repeatedly washed with cumene as a washing agent and then dried for the next cycle of reaction, maintaining the same catalyst-to-reactant ratio as the first cycle. For the reaction solution, a small amount of the reaction solution was analyzed by gas chromatography to determine the molar amount of α-epoxypine. The remaining molar amount of cumene hydrogen peroxide in the reaction solution was titrated with 0.1 mol / L sodium thiosulfate. Based on this, the yield can be calculated. α-环氧蒎烷 and S α-环氧蒎烷 The results are shown in Table 1.
[0118] Example 10
[0119] The titanium-containing SiO2 catalyst prepared in Example 1 was used to synthesize α-epoxypinene via the epoxidation of α-pinene. 5 g of titanium-containing SiO2 catalyst, 50 g of cumene solution, 250 g of α-pinene, 0.5 g of sodium bicarbonate, and 83.6 g of cumene hydrogen peroxide were weighed into a round-bottom flask equipped with a reflux condenser and a magnetic stirrer. After stirring to mix the solution, the flask was transferred to a 65°C constant-temperature water bath, and magnetic stirring was started. The reaction time was calculated, and after 3 hours of reaction, the flask was immediately cooled. The catalyst and reaction solution were then separated by centrifugation. The catalyst was repeatedly washed with cumene as a washing agent and then dried for the next cycle of reaction, maintaining the same catalyst-to-reactant ratio as the first cycle. For the reaction solution, a small amount of the reaction solution was analyzed by gas chromatography to determine the molar amount of α-epoxypine. The remaining molar amount of cumene hydrogen peroxide in the reaction solution was titrated with 0.1 mol / L sodium thiosulfate. Based on this, the yield can be calculated. α-环氧蒎烷 and S α-环氧蒎烷 The results are shown in Table 1.
[0120] Example 11
[0121] The titanium-containing SiO2 catalyst prepared in Example 1 was applied to the epoxidation reaction of α-pinene to synthesize α-epoxypinene. 5 g of titanium-containing SiO2 catalyst, 60 g of tert-butanol solution, 250 g of α-pinene, 0.5 g of sodium bicarbonate, and 81.6 g of tert-butyl hydroperoxide decane solution were weighed into a round-bottom flask equipped with a reflux condenser and a magnetic stir bar. After stirring to mix the solution, the flask was transferred to a 65°C constant-temperature water bath, and magnetic stirring was started. The reaction time was calculated, and after 2 hours of reaction, the flask was immediately cooled. The catalyst and reaction solution were then separated by centrifugation. The catalyst was repeatedly washed with cumene as a washing agent and then dried for the next cycle of reaction, maintaining the same catalyst-to-reactant ratio as the first cycle. For the reaction solution, a small amount of the reaction solution was analyzed by gas chromatography to determine the molar amount of α-epoxypine. The remaining molar amount of cumene hydrogen peroxide in the reaction solution was titrated with 0.1 mol / L sodium thiosulfate. Based on this, the yield can be calculated. α-环氧蒎烷 and S α-环氧蒎烷 The results are shown in Table 1.
[0122] Example 12
[0123] The titanium-containing SiO2 catalyst prepared in Example 1 was used to synthesize α-epoxypinene via the epoxidation of α-pinene. 5 g of titanium-containing SiO2 catalyst, 60 g of tert-butanol solution, 250 g of α-pinene, 0.5 g of sodium bicarbonate, and 81.6 g of tert-butyl hydroperoxide decane solution were weighed into a round-bottom flask equipped with a reflux condenser and a magnetic stir bar. After stirring to mix the solution, the flask was transferred to a 75°C constant-temperature water bath, and magnetic stirring was started. The reaction time was calculated, and after 2 hours, the flask was immediately cooled. The catalyst and reaction solution were then separated by centrifugation. The catalyst was repeatedly washed with cumene as a washing agent and then dried for the next cycle of reaction, maintaining the same catalyst-to-reactant ratio as the first cycle. For the reaction solution, a small amount of the reaction solution was analyzed by gas chromatography to determine the molar amount of α-epoxypine. The remaining molar amount of cumene hydrogen peroxide in the reaction solution was titrated with 0.1 mol / L sodium thiosulfate. Based on this, the yield can be calculated. α-环氧蒎烷 and S α-环氧蒎烷 The results are shown in Table 1.
[0124] Table 1
[0125]
[0126]
[0127] As can be seen from the results in Table 1, the examples using the method of the present invention exhibit significantly higher product yields and selectivity. Furthermore, the catalyst described in this invention demonstrates high stability and can be reused more than five times.
[0128] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for the epoxidation reaction of pinene, the method comprising: Under epoxidation reaction conditions, pinene, at least one oxidant, and optionally at least one solvent are contacted with a titanium-containing SiO2 catalyst to obtain a reaction product; the oxidant is a peroxide; the pinene is α-pinene; and the reaction product is α-epoxypinene. The titanium-containing SiO2 catalyst comprises amorphous SiO2, titanium, and fluorine; the Si / Ti molar ratio of the titanium-containing SiO2 catalyst is 25-250; and the Si / F molar ratio is 30-120. The preparation method of the titanium-containing SiO2 catalyst includes: (1) Amorphous SiO2 powder and fluorine source are mixed in an alkaline solution to obtain fluorine-containing SiO2 solid; (2) The fluorine-containing SiO2 solid is loaded with titanium under a protective gas atmosphere to obtain a titanium-containing SiO2 catalyst precursor; (3) The titanium-containing SiO2 catalyst precursor is subjected to water vapor treatment and silane vapor treatment in a protective gas atmosphere to obtain the titanium-containing SiO2 catalyst.
2. The method according to claim 1, wherein, The conditions for the epoxidation reaction include: a temperature of 60-125℃ and a pressure of 0.01-1MPa.
3. The method according to claim 2, wherein, The conditions for the epoxidation reaction include: a temperature of 60-110 ℃ and a pressure of 0.1-0.5 MPa.
4. The method according to claim 1, wherein, The mass ratio of titanium-containing SiO2 catalyst, pinene, and oxidant is 1:(25-150):(5-50).
5. The method according to claim 4, wherein, The mass ratio of titanium-containing SiO2 catalyst, pinene, and oxidant is 1:(50-120):(10-20).
6. The method according to claim 1, wherein, The oxidant is hydrogen peroxide, organic peroxide, or peracid.
7. The method according to claim 6, wherein, The oxidant is tert-butyl hydroperoxide decane and / or cumene hydroperoxide.
8. The method according to claim 1, wherein, The solvent is selected from at least one of water, C1-C6 alcohols and C6-C12 aromatics; The mass ratio of titanium-containing SiO2 catalyst to solvent is 1:(5-45).
9. The method according to claim 8, wherein, The solvent is tert-butanol and / or cumene; The mass ratio of titanium-containing SiO2 catalyst to solvent is 1:(5-20).
10. The method according to any one of claims 1-9, wherein, The contact is carried out in the presence of at least one additive; The additive is selected from at least one of sodium carbonate, sodium bicarbonate, potassium carbonate, and potassium bicarbonate.
11. The method according to claim 10, wherein, The mass ratio of titanium-containing SiO2 catalyst to additive is 1:(0.05-1).
12. The method according to claim 11, wherein, The mass ratio of titanium-containing SiO2 catalyst to additive is 1:(0.05-0.25).
13. The method according to any one of claims 1-9, wherein, The method also includes distilling the contacted materials to obtain the reaction products.
14. The method according to any one of claims 1-9, wherein, The molar ratio of Si / Ti in the titanium-containing SiO2 catalyst is 45-200; the molar ratio of Si / F is 40-90.
15. The method according to any one of claims 1-9, wherein, UV-VIS characterization showed that the titanium-containing SiO2 catalyst had an absorption peak at 210-230 nm.
16. The method according to any one of claims 1-9, wherein, The titanium-containing SiO2 catalyst contains less than 50 ppm of sodium, less than 50 ppm of iron, and less than 50 ppm of potassium.
17. The method according to any one of claims 1-9, wherein, The amount of amorphous SiO2, titanium source, and fluorine source used results in a Si / Ti molar ratio of 25-250 and a Si / F molar ratio of 30-120 in the prepared titanium-containing SiO2 catalyst.
18. The method according to claim 17, wherein, The amount of amorphous SiO2, titanium source, and fluorine source used results in a Si / Ti molar ratio of 45-200 and a Si / F molar ratio of 40-90 in the prepared titanium-containing SiO2 catalyst.
19. The method according to any one of claims 1-9, wherein, The amorphous SiO2 contains sodium, iron, and potassium, wherein the sodium content is below 1000 ppm, the iron content is below 1000 ppm, and the potassium content is below 1000 ppm.
20. The method according to any one of claims 1-9, wherein, The specific surface area of the amorphous SiO2 is 300-500 m². 2 / g, pore size 1-1.8 cm³ 3 / g, with an average pore size of 5-10nm.
21. The method according to any one of claims 1-9, wherein, The mixing in step (1) includes: first mixing amorphous SiO2 powder with an alkaline solution, and then mixing it with a fluorine source.
22. The method according to any one of claims 1-9, wherein, The mixing conditions in step (1) include: a temperature of 25-70℃ and a time of 0.5-8h.
23. The method according to claim 22, wherein, The mixing conditions in step (1) include: a temperature of 40-55℃ and a time of 1-5h.
24. The method according to any one of claims 1-9, wherein, The molar ratio of amorphous SiO2 to fluorine source is 1:30-150, wherein the fluorine source is calculated as F element.
25. The method according to claim 4, wherein, The molar ratio of amorphous SiO2 to fluorine source is 1:30-45, wherein the fluorine source is calculated as F element.
26. The method according to any one of claims 1-9, wherein, The weight ratio of amorphous SiO2 to alkaline solution is 1:5-50.
27. The method according to claim 26, wherein, The weight ratio of the amorphous SiO2 to the alkaline solution is 1:10-35.
28. The method according to any one of claims 1-9, wherein, The molar concentration of the alkaline solution is 0.5-2.5 mol / L.
29. The method according to any one of claims 1-9, wherein, The base is an inorganic base and / or an organic base; the inorganic base is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate; the organic base is selected from at least one of ethylamine, methylamine, and n-butylamine.
30. The method according to claim 29, wherein, The base is selected from at least one of sodium hydroxide, potassium hydroxide, and ethylamine.
31. The method according to any one of claims 1-9, wherein, The fluorine source is selected from at least one of ammonium fluoride, potassium fluoride, and sodium fluoride.
32. The method according to any one of claims 1-9, wherein, The conditions for loading titanium in step (2) include: temperature of 280-750℃ and time of 0.5-6h.
33. The method according to claim 32, wherein, The conditions for loading titanium in step (2) include: temperature of 300-600℃ and time of 0.5-3h.
34. The method according to any one of claims 1-9, wherein, The titanium source is titanium tetrachloride.
35. The method according to any one of claims 1-9, wherein, The protective gas flow rate is 50-300 mL / min relative to 1g of fluorine-containing SiO2 solid.
36. The method according to claim 35, wherein, The protective gas flow rate is 60-100 mL / min relative to 1g of fluorine-containing SiO2 solid.
37. The method according to any one of claims 1-9, wherein, The protective gas is selected from at least one of nitrogen, helium, and argon.
38. The method according to any one of claims 1-9, wherein, The method further includes: before loading titanium in step (2), the fluorine-containing SiO2 solid product is treated under a protective gas atmosphere, and the treatment conditions include: temperature of 150-300℃; time of 1-6h.
39. The method according to claim 38, wherein, The processing conditions include: a temperature of 200-300℃ and a time of 1-3 hours.
40. The method according to any one of claims 1-9, wherein, The conditions for steam treatment in step (3) include: a temperature of 80-600℃ and a time of 0.5-6h.
41. The method according to claim 40, wherein, The conditions for steam treatment in step (3) include: a temperature of 80-500℃ and a time of 0.5-3h.
42. The method according to any one of claims 1-9, wherein, The conditions for the silane vapor treatment include: a temperature of 150-350℃ and a time of 0.5-10h.
43. The method according to claim 42, wherein, The conditions for the silane vapor treatment include: a temperature of 150-250℃ and a time of 0.5-5h.
44. The method according to any one of claims 1-9, wherein, The silane reagent used in the silane vapor treatment is selected from at least one of trimethylchlorosilane, trimethylmethoxysilane, trimethylethoxysilane, trichloromethylsilane, hexamethyldisilazane, and tetramethyldisilazane.
Citation Information
Patent Citations
Method for synthesizing epoxy pinane from pinene
CN112608287A
Method for synthesizing alpha-epoxy pinane through epoxidation of alpha-pinene
CN114591268A
Epoxidizing method of alpha-pinene
CN1438222A
Method for preparing 2,3-pinene oxide through epoxidation of alpha-pinene
CN104119300A